MENINGKATKAN MOTIVASI KERJA KARYAWAN MELALUI PERCEIVED ORGANIZATIONAL SUPPORT, PERSON ORGANIZATION FIT, DAN KOMPENSASI (Studi Pada KPRI NEU RSUD Banyumas) - Amin Budiastuti; Rosalina Anindia Sari Kartika; Guntoro Guntoro (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
The research aims to analyze the effect of perceived organizational support, person-organization fit and compensation on employee’s job mativation. This research conducted at KPRI NEU RSUD Banyumas in December 2020. The type of research is survey method and data were collected based on questionnaires. The population of this study was 112 people. The number of respondents was 53 determined by proportionate stratified random sampling method. Data were analysed using multiple liniear regressions and t-test. The result showed perceived organizational support, person-organization Fit, and compensation have a significant effect on job motivation with the values of tcount which bigger than t table. Organization should make effort to increase job motivation by increasing perceived organization support, person-organization fit, and compensation.